Pelatihan Peningkatan Motivasi Kewirausahaan Bagi Siswa Smu Di Jakarta Selatan - Iha Haryani; Mulyadi; Lies Putriana; Safitri Siswono; Amelia Oktrivina (SULUH: Jurnal Abdimas, 2025)
Nowadays, many students still in schools have succeeded with businesses that they started themselves from scratch. Some can even collect a lot of money from these activities. Many students to be a entrepreneur. A successful entrepreneur or businessperson can either be born or developed. Born is related to the children’s talents and potentials inherent in them when they were born. However, talent and potential alone are not enough to make someone a successful entrepreneur. Being developed is also another important factor in shaping the characters and the personalities by equipping the children with knowledge, skills and a supportive environment. For that reason, the Faculty of Economics and Business Team from University of Pancasila held community service activities by conducting training activities to increase entrepreneurial motivation of students of MAN 7 Jakarta. The purpose of the training activity is high school students in the forms of: self-reflections to know their personality types; awareness that building successful business ventures cannot be done overnight but requires hard work, a mature plan, and a super supporting team to achieve business goals; handling financial problems due to the importance of financial reports to make a decision and to compile business strategies to achieve sustainable businesses. The effectiveness of this traning can be evaluated by comparing the scores of the assessment before and after the community service activities. The results are: the training activities were attended by 36 students of MAN 7 Jakarta, consisting of 58% male students and 42% female students, aged between 16-18 years. Most of these students have sanguine (31%) and melancholic (31%) potential types. The activities went smoothly and were beneficial for students, and the level of students' entrepreneurial knowledge increased. There were three materials presented. The assesment of the two materials (knowing yourself and the importance of financial reports) show the increase of the scores after the training (S-B). On the other hand, the assesment of the other material (the spirit of entrepreneurial motivation) reveals no change in the scores. In addition, out of 14 statements, six were considered by the students to be better after the training (S-B). two other statements to be equally good before and after the training (B-B). Only six statements were considered by students to be equally moderate before and after the training (S-S).